1993
DOI: 10.1227/00006123-199306000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Spinal Accessory Nerve Injury

Abstract: Eighty-three consecutive patients with extracranial accessory nerve injury seen over a 12-year period are reviewed. The most common etiology was iatrogenic injury to the nerve at the time of previous surgery. Such operations were usually minor in nature and often related to lymph node or benign tumor removal. Examination usually distinguished winging due to trapezius weakness from that of serratus anterior palsy. Trapezius weakness was seen in all cases. Sternocleidomastoid weakness was unusual. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 12 publications
0
47
1
6
Order By: Relevance
“…In cases of iatrogenic XIth nerve injury, many studies have found that surgical repair gives generally good results: Williams et al 3 repaired 39 accessory nerves by either grafting or neurolysis and found 32 of these patients had improved symptoms of shoulder pain and weakness. Donner et al 1 repaired 31 nerves, most showing similar postoperative improvement. Weisberger 13 performed cable grafting of 20 nerves post-neck dissection, and found that resulting shoulder strength, function, and electromyography results were intermediate when compared to patients without XIth nerve injury and those with XIth nerve injury which was not repaired.…”
Section: Discussionmentioning
confidence: 97%
“…In cases of iatrogenic XIth nerve injury, many studies have found that surgical repair gives generally good results: Williams et al 3 repaired 39 accessory nerves by either grafting or neurolysis and found 32 of these patients had improved symptoms of shoulder pain and weakness. Donner et al 1 repaired 31 nerves, most showing similar postoperative improvement. Weisberger 13 performed cable grafting of 20 nerves post-neck dissection, and found that resulting shoulder strength, function, and electromyography results were intermediate when compared to patients without XIth nerve injury and those with XIth nerve injury which was not repaired.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][7][8][9][10][11] This probably is because in the earlier reports the injuries predominantly occurred as a result of lymph node biopsy procedures (a punctate lesion). [3][4][5][6][7][8][9][10][11] All of our patients had surgery after extended palsy, and this long interval between injury and repair probably accounts for progressive retraction and scarring of the nerve stumps with a resultant wider gap between the nerve ends. Experimentally, we showed that the length of the nerve graft interferes with the recovery of mixed nerves.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several investigators 3-12 have described series of patients with traumatic transection of the accessory nerve who have been explored and had the division repaired with good functional results. All of these surgeons, [3][4][5][6][7][8][9][10][11][12] however, characterized the surgery as difficult. Often a mixture of scar, blood vessels, lymph nodes, and adipose tissue occupies the region between the posterior border of the sternocleidomastoid muscle and the anterior border of the trapezius muscle, rendering identification of the nerve stumps laborious.…”
mentioning
confidence: 99%
“…Conservative treatment and physical therapy for spinal accessory nerve injuries have been shown to be unsuccessful because of the inability to adequately strengthen adjacent muscle groups to compensate for the trapezius palsy. 3,4,6,10,12,15,18,19 Therefore, the modified Eden-Lange procedure was chosen as the surgical treatment for our patient's lateral scapular winging. This procedure allowed him to achieve good results in terms of pain relief, strength, and stability after a routine physical therapy program (Table I).…”
Section: Discussionmentioning
confidence: 99%